2018
DOI: 10.3892/mmr.2018.8895
|View full text |Cite
|
Sign up to set email alerts
|

Integrated bioinformatics analysis reveals key candidate genes and pathways in breast cancer

Abstract: Breast cancer (BC) is the leading malignancy in women worldwide, yet relatively little is known about the genes and signaling pathways involved in BC tumorigenesis and progression. The present study aimed to elucidate potential key candidate genes and pathways in BC. Five gene expression profile data sets (GSE22035, GSE3744, GSE5764, GSE21422 and GSE26910) were downloaded from the Gene Expression Omnibus (GEO) database, which included data from 113 tumorous and 38 adjacent non-tumorous tissue samples. Differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…The immunohistochemical results were verified via the Human Protein Atlas (HPA; ) (29,30). The website aims at mapping the distribution of human proteins in cells, tissues and organs using integration technologies.…”
Section: Methodsmentioning
confidence: 99%
“…The immunohistochemical results were verified via the Human Protein Atlas (HPA; ) (29,30). The website aims at mapping the distribution of human proteins in cells, tissues and organs using integration technologies.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, genes and signaling pathways that participate in breast cancer tumorigenesis and progression remain to be further investigated. Exploring new genes and pathways associated with breast cancer may help to identify potential molecular mechanisms, diagnostic markers and therapeutic targets (Wang et al, 2018). High-throughput genomic analysis techniques can be applied to screening for differentially expressed genes (DEGs) and to understand the relevant pathways and protein interaction networks (Vogelstein et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The combined application of these valuable microarray data allows us to build high-resolution networks (Fig 2) that contain useful information to detect gene regulatory networks in biological processes [7]. This suggests that we can perform co-expression screening using reliable network datasets and an effective human cancer database to track the genes involved in specific biological events [11]. In this study, 62 genes with high correlation with ITGA11 were identified as hub genes based on the UniProtKB keyword enrichment analysis.…”
Section: Discussionmentioning
confidence: 83%